(1)(-16-50+3又5分之2)÷(-2)(2)(-6)×8-(-2)³-(-4)²×5(3)(-2分之1)²+2分之1×(3分之2-│3分之2-2│)(4)-1-(1-0.5)×3分之1
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 16:10:56
(1)(-16-50+3又5分之2)÷(-2)(2)(-6)×8-(-2)³-(-4)²×5(3)(-2分之1)²+2分之1×(3分之2-│3分之2-2│)(4)-1-(1-0.5)×3分之1
(1)(-16-50+3又5分之2)÷(-2)(2)(-6)×8-(-2)³-(-4)²×5
(3)(-2分之1)²+2分之1×(3分之2-│3分之2-2│)(4)-1-(1-0.5)×3分之1
(1)(-16-50+3又5分之2)÷(-2)(2)(-6)×8-(-2)³-(-4)²×5(3)(-2分之1)²+2分之1×(3分之2-│3分之2-2│)(4)-1-(1-0.5)×3分之1
(1) (-16-50+3又5分之2)÷(-2)
=(-66+17/5)÷(-2)
=33-17/10
=313/10
=31.3
(2) (-6)×8-(-2)³-(-4)²×5
=-48+8-16×5
=-40-80
=-120
(3) (-2分之1)²+2分之1×(3分之2-│3分之2-2│)
=1/4+1/2×(2/3-2+2/3)
=1/4+1/2×(4/3-2)
=1/4+(2/3-1)
=1/4+2/3-1
=-1/12
(4) -1-(1-0.5)×3分之1
=-1-0.5×1/3
=-1-1/6
=-7/6
(1)(-16-50+3又5分之2)÷(-2)
=-62.6÷(-2)
=31.3
(2)(-6)×8-(-2)³-(-4)²×5
=-48+8-80
=-120
(3)(-2分之1)²...
全部展开
(1)(-16-50+3又5分之2)÷(-2)
=-62.6÷(-2)
=31.3
(2)(-6)×8-(-2)³-(-4)²×5
=-48+8-80
=-120
(3)(-2分之1)²+2分之1×(3分之2-│3分之2-2│)
=1/4+1/12
=1/3
(4)-1-(1-0.5)×3分之1
=-1-1/6
=-1又1/6
希望对你有帮助
收起